2019
DOI: 10.3390/met9050594
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Filler Wire Dilution Using External Oscillating Magnetic Field at Full Penetration Hybrid Laser-Arc Welding of Thick Materials

Abstract: Hybrid laser-arc welding offers many advantages, such as deep penetration, good gap bridge-ability, and low distortion due to reduced heat input. The filler wire which is supplied to the process is used to influence the microstructure and mechanical properties of the weld seam. A typical problem in deep penetration high-power laser beam welding with filler wire and hybrid laser-arc welding is an insufficient mixing of filler material in the weld pool, leading to a non-uniform element distribution in the seam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In these studies, the magnet was operated on the top side during wire-feed LBW in partial penetration mode. With a magnet operating at the bottom side to prevent sagging as well as to improve the filler wire mixing at single-pass HLAW of steel plates with a wall thickness of 20 mm and above was demonstrated in previous studies [16,17]. Therefore, an AC magnet was positioned under the workpiece and operated at a magnetic flux density of approx.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the magnet was operated on the top side during wire-feed LBW in partial penetration mode. With a magnet operating at the bottom side to prevent sagging as well as to improve the filler wire mixing at single-pass HLAW of steel plates with a wall thickness of 20 mm and above was demonstrated in previous studies [16,17]. Therefore, an AC magnet was positioned under the workpiece and operated at a magnetic flux density of approx.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies dealing with laser beam based welding by use of an oscillating magnetic field, it could be shown that the melt flow dynamic could be influenced positive to e.g. reduce the porosity of laser beam welded aluminum die casting [17] or to improve the transport of the filler wire elements at hybrid laser arc welding through formation of a vortex within the melt pool [18]. This study deals with the influence of an external oscillating magnetic field during highpower laser beam welding on the keyhole stability and on the laser beam incident angle.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding (FSW) seems to relieve some of these problems [16]. In this context, HLAW processes with a laser source seem to be a promising technology to join HSLA steels in shipbuilding [2,21].…”
Section: Introductionmentioning
confidence: 99%